Antimicrobial Peptide Delivery Systems as Promising Tools Against Resistant Bacterial Infections - Kamila Botelho Sampaio de Oliveira; Michel Lopes Leite; Nadielle Tamires Moreira Melo; Letícia Ferreira Lima; Talita Cristina Queiroz Barbosa; Nathalia Lira Carmo; Douglas Afonso Bittencourt Melo; Hugo Costa Paes; Octávio Luiz Franco (MDPI AG, 2024)
The extensive use of antibiotics during recent years has led to antimicrobial resistance development, a significant threat to global public health. It is estimated that around 1.27 million people died worldwide in 2019 due to infectious diseases caused by antibiotic-resistant microorganisms, according to the WHO. It is estimated that 700,000 people die each year worldwide, which is expected to rise to 10 million by 2050. Therefore, new and efficient antimicrobials against resistant pathogenic bacteria are urgently needed. Antimicrobial peptides (AMPs) present a broad spectrum of antibacterial effects and are considered potential tools for developing novel therapies to combat resistant infections. However, their clinical application is currently limited due to instability, low selectivity, toxicity, and limited bioavailability, resulting in a narrow therapeutic window. Here we describe an overview of the clinical application of AMPs against resistant bacterial infections through nanoformulation. It evaluates metal, polymeric, and lipid AMP delivery systems as promising for the treatment of resistant bacterial infections, offering a potential solution to the aforementioned limitations.